The LEGO Arduino cookbook : expanding the realm of MINDSTORMS EV3 invention - Koch, Grady (Apress, 2020)
Push into new fields of technology using LEGO and Arduino with the projects in this Cookbook. MINDSTORMS EV3 inventions don't have to be confined to LEGO factory-made sensors. Incorporate a wide range of sensors, displays, LED arrays, actuators, and even a smartphone into your creations. Add amazing capabilities to your LEGOs by building things such as a metal detector, long-range lidar, audio spectrum analyzer, weather station, and a smartphone. Step-by-step instructions bring these new devices to life. You'll work with the reliable and inexpensive Arduino UNO to take your projects even further and make them truly smart. Learn to set up and program your Arduino UNO. Then learn data communications protocols (I2C, SPI, and PWM) to link sensors to the Arduino. A variety of data communications techniques are also demonstrated on passing data between the Arduino and the MINDSTORMS EV3 Intelligent Brick. Equipped with these new tools, LEGO inventors can build vast new capabilities into their designs. What You'll Learn Interface new sensors, devices, and communications with LEGO Mindstorms EV3 Work with communication protocols of pulse width modulation (PWM), I2c, and SPI Convert pulse width modulation to analog voltage with resistor and capacitor components Who This Book Is For Tech savvy fans of LEGO projects and hardware hackers. Also coaches or students involved in a school science/technology project or design competition.